2003
DOI: 10.1007/s00244-002-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Naled on Honey Bee Apis mellifera L. Survival and Productivity: Aerial ULV Application Using a Flat-Fan Nozzle System

Abstract: A study was conducted to evaluate the impact of naled on honey bees as a result of their exposure to aerial ULV applications of this insecticide during three routine mosquito spray missions by Manatee County Mosquito Control District in Florida during the summer of 1999. Naled deposits were collected on filter paper and subsequently analyzed by gas chromatography. Mortality of adult honey bees Apis mellifera L. was estimated based on numbers from dead bee collectors placed in front of the entrance of the beehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Gil and Sinfort (2005) indicated that drifting spray is a complex problem in which equipment design and application parameters spray physical properties and formulation and meteorological conditions interact and influence pesticide loss. Zhong et al (2003) conducted a study to evaluate the impact of naled on honey bees as a result of their exposure to aerial ultralow volume (ULV) applications of this insecticide during three routine mosquito spray missions. They indicated that insecticide deposit around the hives could be influenced by environmental factors, such as wind speed and site topography.…”
Section: Introductionmentioning
confidence: 99%
“…Gil and Sinfort (2005) indicated that drifting spray is a complex problem in which equipment design and application parameters spray physical properties and formulation and meteorological conditions interact and influence pesticide loss. Zhong et al (2003) conducted a study to evaluate the impact of naled on honey bees as a result of their exposure to aerial ultralow volume (ULV) applications of this insecticide during three routine mosquito spray missions. They indicated that insecticide deposit around the hives could be influenced by environmental factors, such as wind speed and site topography.…”
Section: Introductionmentioning
confidence: 99%
“…There was no effect on hive weight or health of the colony over a season. Zhong et al (2004) and Zhong et al (2003) observed similar results with aerially applied Manuscript to be reviewed naled and noted that bees clustering outside of the hive (termed "bearding") were most susceptible.…”
Section: Discussionmentioning
confidence: 63%
“…Aerial application of Aqua-K-Othrine (2% deltamethrin) and Pesguard S102 (10% d-phenothrin) showed no significant mortality relative to the controls, and exposed colonies had the same number of frames of adult bees, brood population, and colony weight as the control (Chaskopoulou et al , 2014). While aerial application of naled resulted in significantly higher numbers of dead honey bees than the control treatment, exposed colonies produced as much honey as the control colonies (Zhong et al , 2003). A small number of dead bees in proportion to colony size is likely to have little impact on an otherwise healthy colony as the number of workers that die from insecticide exposure would have to be more than twice the rate of those which die naturally for more than 35 days (Henry et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One hour after malathion application, residues on foraged pollen was sufficient to kill bees (Pankiw & Jay, 1992). In addition, acute bee kills have been reported to occur following mosquito adulticiding operations with naled or malathion (Dixon & Fingler, 1984; Hester et al , 2001; Zhong et al , 2003).…”
Section: Introductionmentioning
confidence: 99%